The functional model of the library - V. N. Markova (Библиосфера, 2013)
In article an attempt to study functions of the modern library under the influence of globalization, informatization and cultural transformation of society is made. The basic approaches to management of modern library are comprehended. The functional model of library management is offered, which in the author’s opinion corresponds to the modern conditions.